Customer welfare of Sharia microfinance institutions: Ease of access, product expertise, and the mediating role of service quality - Kuat Ismanto; Ina Mutmainah (Faculty of Islamic Economics and Business, UIN Salatiga, 2024)
Baitul Maal wat Tamwil (BMT) is vital in developing Micro, Small, and Medium Enterprises (MSMEs). This paper examines the benefits of BMT for members regarding accessibility, product expertise, and service quality. This study was designed with quantitative methods using a survey by distributing questionnaires to 200 respondents gathered from five branch offices of BMT Bahtera, Pekalongan, Indonesia. This study employed path analysis to analyze the data. The study results demonstrate that accessibility, product expertise, and service quality significantly impacted consumer welfare. This result indicates that customer welfare is the primary factor in the growth of BMTs. Conversely, accessibility, product expertise, and service quality were significant for BMT growth and members’ welfare. This research contributes to BMT product quality improvement and ease of access to customer services by using technology to create effectiveness and efficiency.